Workplace incivility as a moderator of the relationships between polychronicity and job outcomes - Arasli, Huseyin; Namin, Boshra Hejraty; Abubakar, A. Mohammed (Emerald Group Publishing Ltd, 2018)
Purpose - On the basis of person-job fit theory and conservation of resource theory, this study aims to develop and test a model to examine the impact of polychronicity on frontline employees' job performance in hotel industry and simultaneously, investigate the moderating effects of supervisor, coworker and customer incivility as stressors in the relationship between polychronicity and employees' job performance. Design/methodology/approach - Data are obtained in North Cyprus from 262 frontline employees working in four- and five-star hotels. Findings - The results suggest that polychronicity refers to employees' performance. Customer incivility negatively and significantly influences job performance, but coworker and supervisor incivilities do not. Unlike coworker incivility, both customer and supervisor incivilities moderate the relationship between polychronicity and job performance; that is, high customer and/or supervisor incivility weaken the positive relationship between polychronicity and job performance. Practical implications - Regarding the critical role of polychronic frontline employees, hotel management should recruit the right candidates and endeavor to retain such employees by offering monetary and non-monetary incentives, training and empowering. They may implement a zero-tolerance policy that simultaneously supports both parties (customers and employees). Originality/value - The association between employee quality (i.e. polychronicity), job performance and incivility is often overlooked in the hospitality research. This study is the first attempt to consider the joint moderating effect of important social stressors (customer, coworker and supervisor incivility) in the hotel industry.
Keywords: Job performance; Hotel; Incivility; Polychronicity; Frontline